2014
DOI: 10.1016/j.orgel.2014.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Color-stable, ITO-free white organic light-emitting diodes with enhanced efficiency using solution-processed transparent electrodes and optical outcoupling layers

Abstract: In this work, we demonstrate color-stable, ITO-free white organic light-emitting diodes (WOLEDs) with enhanced efficiencies by combining the high-conductivity conducting polymer PEDOT:PSS as transparent electrode and a nanoparticle-based scattering layer (NPSL) as the effective optical out-coupling layer. In addition to efficiency enhancement, the NPSL is also beneficial to the stabilization of electroluminescent spectra/colors over viewing angles. Both the PEDOT:PSS and the NPSL can be fabricated by simple, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…40 For a scattering structure to be effective for a particular mode, photons trapped within this mode must be likely to be scattered before they are lost, i.e., the modal scattering length (¼scattering length × overlap of mode with scattering structure) has to be smaller than or comparable to the decay length of the modes that are to be extracted. 56 Recently, Li et al combined the nanoparticle scattering approach with flexible nanocomposite electrodes comprising single-walled carbon nanotubes (CNTs) and silver nanowires, again leading to a considerable increase in outcoupling efficiency. Figure 5 shows mode profiles of the lowest-order waveguided and plasmonic mode supported by a standard bottom-emitting OLED stack and how these modes can interact with a scattering structure located underneath the anode of the device.…”
Section: Wavelength-independent Scattering-based Outcoupling Approachesmentioning
confidence: 99%
“…40 For a scattering structure to be effective for a particular mode, photons trapped within this mode must be likely to be scattered before they are lost, i.e., the modal scattering length (¼scattering length × overlap of mode with scattering structure) has to be smaller than or comparable to the decay length of the modes that are to be extracted. 56 Recently, Li et al combined the nanoparticle scattering approach with flexible nanocomposite electrodes comprising single-walled carbon nanotubes (CNTs) and silver nanowires, again leading to a considerable increase in outcoupling efficiency. Figure 5 shows mode profiles of the lowest-order waveguided and plasmonic mode supported by a standard bottom-emitting OLED stack and how these modes can interact with a scattering structure located underneath the anode of the device.…”
Section: Wavelength-independent Scattering-based Outcoupling Approachesmentioning
confidence: 99%
“…[1] Yet it is generally found that even with optimized OLED layer structures, planar low-index electrode OLEDs would still exhibit lower optical out-coupling efficiencies than planar high-index ITO devices. [1,2] This dilemma of the low-index electrode (i.e., increased optical coupling into the substrate but decreased optical out-coupling into air) may be mitigated by using a structure that can more converge radiation into the substrate (i.e., less divergent in angles) but not reduce the optical coupling efficiency into the substrate. We find that by inserting a high-index underlayer between the low-index electrode and the substrate can significantly enhance the optical out-coupling efficiency of OLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…3-10 Among them, the conducting polymer poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) has attracted much attention due to its excellent mechanical flexibility, good transmittance and conductivity, solution processing capability, and low cost. [6][7][8][9][10] Various methods to improve the performance of PEDOT:PSS (particularly, the conductivity) had been recently reported and high-conductivity PEDOT:PSS had been successfully used as ITO-free transparent electrodes for OLEDs as well as organic solar cells. [6][7][8][9][10] Previous works on high-conductivity (high-r) PEDOT: PSS and applications for organic optoelectronics mainly focused on its optical transmittance, electrical properties, solution processing capability, and maybe also flexibility.…”
mentioning
confidence: 99%
“…[6][7][8][9][10] Various methods to improve the performance of PEDOT:PSS (particularly, the conductivity) had been recently reported and high-conductivity PEDOT:PSS had been successfully used as ITO-free transparent electrodes for OLEDs as well as organic solar cells. [6][7][8][9][10] Previous works on high-conductivity (high-r) PEDOT: PSS and applications for organic optoelectronics mainly focused on its optical transmittance, electrical properties, solution processing capability, and maybe also flexibility. [6][7][8][9][10] Intriguingly, PEDOT:PSS indeed also has a low optical refractive index (n) of $1.5, significantly lower than those of ITO (n $ 1.8-2.1) and typical organic layers in OLEDs (n $ 1.7-1.8) and well matching that of typical OLED substrates (n $ 1.5 for general glass and plastic substrates).…”
mentioning
confidence: 99%
See 1 more Smart Citation